Is anonymity dead?: Doing critical research on digital labour platforms through platform interfaces. (14th May 2022) - Spilda, Funda Ustek; Howson, Kelle; Johnston, Hannah; Bertolini, Alessio; Feuerstein, Patrick; Bezuidenhout, Louise; Alyanak, Oğuz; Graham, Mark
Abstract : Critical research into the gig economy frequently relies on using platform interfaces, platform mobile applications or websites, as intermediaries to contact and recruit participants. Yet, these methods are accompanied by significant ethical implications that are rarely considered. In this article, we look at the organisational features of platform interfaces for research and explore the ways in which, through their intensive knowledge about their users, they present additional challenges to researchers' abilities to (a) conduct independent research – for example by influencing the participant recruitment process and (b) establish and maintain respondent anonymity and researcher transparency. Our analysis is based on an international study of platform workers which investigates working conditions and fairness in the gig economy in both geographically tethered gig work and cloudwork. We argue that the ethical boundaries of doing research through platform interfaces are shaped not only by researchers, but also by the platforms whose interfaces researchers use. Establishing and protecting the anonymity of research participants provides an acute example of this, as platforms have the potential to scrutinise the activities of researchers on their interfaces, and capture information shared between researchers and participants. The question of anonymity arises also in the reverse order: when platforms share personal information on workers, at a level not required by researchers. After building our argument, we propose a set of suggestions for promoting ethical research in the study of gig economy platforms.